2009
DOI: 10.1523/jneurosci.0201-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Brain Injury Does Not Alter the Intrinsic Differentiation Potential of Adult Neuroblasts

Abstract: Neuroblasts produced by the neural stem cells of the adult subventricular zone (SVZ) migrate into damaged brain areas after stroke or other brain injuries, and previous data have suggested that they generate regionally appropriate new neurons. To classify the types of neurons produced subsequent to ischemic injury, we combined BrdU or virus labeling with multiple neuronal markers to characterize new cells at different times after the induction of stroke. We show that SVZ neuroblasts give rise almost exclusivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(110 citation statements)
references
References 59 publications
7
103
0
Order By: Relevance
“…The implication of heterogeneous brain stem cells for tissue regeneration is not well understood. However, the limited availability or depletion of specific stem and progenitor cells could impair the regeneration of specific brain cell lineages (Liu et al, 2009;Encinas et al, 2011;Barbosa et al, 2015). Teleost fish have a much greater ability to regenerate CNS injuries than mammals (Becker et al, 1997;Kaslin et al, 2008;Reimer et al, 2008;Kroehne et al, 2011;Baumgart et al, 2012;Kishimoto et al, 2012;Kizil et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The implication of heterogeneous brain stem cells for tissue regeneration is not well understood. However, the limited availability or depletion of specific stem and progenitor cells could impair the regeneration of specific brain cell lineages (Liu et al, 2009;Encinas et al, 2011;Barbosa et al, 2015). Teleost fish have a much greater ability to regenerate CNS injuries than mammals (Becker et al, 1997;Kaslin et al, 2008;Reimer et al, 2008;Kroehne et al, 2011;Baumgart et al, 2012;Kishimoto et al, 2012;Kizil et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Inta and Gass (2015) reported ECT-triggered neurogenesis in striatal and frontal brain regions following ECT in a rat model suggesting that cell proliferation extends beyond the hippocampus. Others (Liu et al, 2009) have also reported increased subventricular zone neuroblast cell proliferation to striatal areas following seizures. Further, ECT-related structural neuroplasticity is shown in the amygdala (Tendolkar et al, 2013;Joshi et al, 2015).…”
Section: Discussionmentioning
confidence: 89%
“…The main differences between germinal-layer-derived and parenchymal neurogenesis are listed in Table 2. It has been proposed that some parenchymal newborn neurons have a transient existence (Gould et al 2001;Luzzati et al 2011), and their fate and role remain unknown (Arvidsson et al 2002;Chen et al 2004;Liu et al 2009;Ohira et al 2010;Bonfanti and Peretto 2011;Luzzati et al 2011).…”
Section: Parenchymal Neurogenesismentioning
confidence: 99%